2010
DOI: 10.1007/s00244-010-9518-1
|View full text |Cite
|
Sign up to set email alerts
|

Mixture Toxicity of SN2-Reactive Soft Electrophiles: 1. Evaluation of Mixtures Containing α-Halogenated Acetonitriles

Abstract: The concept of multiple modes of toxic action denotes that an individual chemical can induce two or more toxic effects within the same series of concentrations, for example, reactive toxicity and narcosis. It appears that such toxicity confounds the ability to develop precise predictions of mixture toxicity and makes it more difficult to clearly link a dose-additive combined effect to agents in the mixture having a single common mechanism of toxic action. This initial study of a three-part series begins to exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
53
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(58 citation statements)
references
References 28 publications
4
53
0
Order By: Relevance
“…The RC 50 values, concentrations that eliminated 50% of the initial free thiol, were 0.559 mM and 0.973 mM for IAM and BAM respectively (Table 1). These data were consistent with the I > Br > Cl pattern of reactivity in a larger group of α-halogenated carbonyl compounds (Dawson et al, 2010; Dawson et al, 2011; Schultz et al, 2007). …”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…The RC 50 values, concentrations that eliminated 50% of the initial free thiol, were 0.559 mM and 0.973 mM for IAM and BAM respectively (Table 1). These data were consistent with the I > Br > Cl pattern of reactivity in a larger group of α-halogenated carbonyl compounds (Dawson et al, 2010; Dawson et al, 2011; Schultz et al, 2007). …”
Section: Resultssupporting
confidence: 86%
“…In fact, experiments with α,β-unsaturated carbonyl derivatives, showed additive toxicity in binary and ternary mixtures in vitro and in an in vivo model (Zhang et al, 2016). Work by Dawson and colleagues showed that HANs and halogenated ethyl acetates (α-halogenated carbonyl containing compounds) generated, in some cases, dose additive toxicity within and among these chemical classes (Dawson et al, 2010; Dawson et al, 2011; Dawson et al, 2014). Additive genotoxicity was observed in binary mixtures of BAM and BAN (Pals et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…These data support the hypothesis that the soft electrophiles in this DBP mixture have a cumulative toxicity and support previous findings of dose additivity in S N 2-reactive electrophiles. 1214 …”
Section: Resultsmentioning
confidence: 99%
“…911 Dawson et al investigated cumulative toxicity of S N 2-reactive haloacetonitriles (HANs) and ethyl- α -halogenated acetates and reported some instances of dose additive toxicity within and among these chemical classes. 1214 The electrophiles within these classes reacted with glutathione (GSH) in chemico ; the reported dose additive toxicity may be attributed to collective GSH depletion as a shared mechanism or molecular initiating event (MIE). 1214 Investigating S N 2-reactive compounds or GSH-depleting agents as a CMG may aid in evaluating additive toxicity within complex DBP mixtures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation